Legal protection of the human right in a healthy environment in Iraqi law - et.al, Haider Suhail Omran , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Environmental protection is currently one of the most important problems facing the countries of the world, and one of the most complex difficulties that preoccupy human societies, peoples, groups, and individuals. The study relied on the analytical research method, and It dealt with the analysis the texts of the Environmental Protection and Improvement Law No. 27 of 2009 and to take note of the provisions and mechanisms decided by the Iraqi legislator to protect and improve the Iraqi environment in the aforementioned law. In order to reach a full presentation of the research topic, the research was divided into five demands, the first was devoted to defining the term legally evidence, the second dealt with the types of environment, while the third was devoted to the legal basis for the administration’s authority to protect the environment, and the fourth was devoted to the department concerned with environmental protection, and was devoted The fifth is for means of protecting the environment from the harmful effects of pollution, then the research ended with a conclusions that summarizes its findings and suggested recommendations regarding its topic. In view of the development in all industrial and agricultural fields and the great environmental damage that resulted from this development, and in order to maintain a healthy environment free of pollutants, the Iraqi legislature initiated the issuance of the Environment Protection and Improvement Law No. 27 of 2009 in order to advance the environmental reality in the country. The law came in line with environmental developments, but the mechanisms taken by the administrative authorities in implementing this law are weak, which led to this weakness to the deterioration of the environmental reality in the country, In order to develop these mechanisms, we suggest that a higher council for environmental protection be formed, linked to the prime minister, that monitors the implementation of the mechanisms by the administrative authorities concerned with the environmental aspect.